Carbohydrate recognition in the immune system: contributions of neoglycolipid‐based microarrays to carbohydrate ligand discovery. (8th July 2013) - Feizi, Ten
Abstract : Oligosaccharide sequences in glycomes of eukaryotes and prokaryotes are enormously diverse. The reasons are not fully understood, but there is an increasing number of examples of the involvement of specific oligosaccharide sequences as ligands in protein–carbohydrate interactions in health and, directly or indirectly, in every major disease, be it infectious or noninfectious. The pinpointing and characterizing of oligosaccharide ligands within glycomes has been one of the most challenging aspects of molecular cell biology, as oligosaccharides cannot be cloned and are generally available in limited amounts. This overview recounts the background to the development of a microarray system that is poised for surveying proteomes for carbohydrate‐binding activities and glycomes for assigning the oligosaccharide ligands. Examples are selected by way of illustrating the potential of "designer" microarrays for ligand discovery at the interface of infection, immunity, and glycobiology. Particularly highlighted are sulfo‐oligosaccharide and gluco‐oligosaccharide recognition systems elucidated using microarrays.